Development of Novel 2D Composites of Silk Sericin and Rice Starch and Application as Bio‐Compatible Scaffold for Cell Culturing. (17th May 2018) - Dutta, Saranga; Dutta, Himjyoti; Devi, Dipali
Abstract : Sericin and starch are waste materials of the silk and rice milling industries, respectively. Owing to their suitable physicochemical, mechanical and functional properties, the two materials are thermo‐mechanically conjugated and cast as films. Sericin forms a microfibrillar network structure which binds with gelatinized starch. Addition of crosslinkers, namely glycerol and polyethylene glycol results in smoother textured films, higher crystallinity, and thermal resistance as studied using XRD, FTIR, DSC, and TGA. Native crystalline patterns of both starch and sericin are lost during composite formation. Newer crystalline lamellae formation with enhanced crystallinity than the native materials is evident from XRD and DSC. Comparative analysis indicated polyethylene glycol to be a better cross linker than glycerol for the composite formation. Biocompatibility studies using L929 mice fibroblast cell lines demonstrated that the films supported normal growth and proliferation of cells without any toxic effect. This is well supported by fluorescence imaging and MTT assays. Enzymatic biodegradability using protease enzymes implied negligible weight loss of the films, strengthening their prospect to be manifested in cell culturing applications. Abstract : Sericin and starch are successfully conjugated to cast films using glycerol and polyethylene glycol as crosslinkers. The films can be used as scaffolds for culturing L929 cells showing normal growth and proliferation without any toxic effects as supported by fluorescence imaging and MTT assays.